2008
DOI: 10.1037/1040-3590.20.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Whose depression relates to discrepancies? Testing relations between informant characteristics and informant discrepancies from both informants' perspectives.

Abstract: This study examined whether mothers' and children's depressive symptoms were each uniquely related to mother-child rating discrepancies on a multidimensional dyadic construct: domains associated with parental monitoring (i.e., Child Disclosure, Parental Knowledge, and Parental Solicitation). Participants included a community sample of 335 mother/female-caregiver and child dyads (182 girls, 153 boys; 9−16 years old). Children's depressive symptoms were consistently related to each of the three domains of mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
104
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(119 citation statements)
references
References 75 publications
14
104
1
Order By: Relevance
“…In particular, incongruence defined by adolescents holding more negative perceptions of the family environment than parents was associated with higher levels of adolescent depressive symptoms and perceived stress. Similar results have also been obtained using directional difference scores (De Los Reyes et al 2008Guion et al 2009;Ferdinand et al 2004). The current study, as well as work using polynomial regression (Laird and De Los Reyes 2013), suggests that these associations may not entirely be a function of methodological artifacts.…”
Section: Does Adolescent-parent Incongruence Predict Adolescents' Psysupporting
confidence: 87%
See 1 more Smart Citation
“…In particular, incongruence defined by adolescents holding more negative perceptions of the family environment than parents was associated with higher levels of adolescent depressive symptoms and perceived stress. Similar results have also been obtained using directional difference scores (De Los Reyes et al 2008Guion et al 2009;Ferdinand et al 2004). The current study, as well as work using polynomial regression (Laird and De Los Reyes 2013), suggests that these associations may not entirely be a function of methodological artifacts.…”
Section: Does Adolescent-parent Incongruence Predict Adolescents' Psysupporting
confidence: 87%
“…As such, the direction of adolescent-parent discrepancies, not just the overall amount, may matter in the context of adolescent adjustment. This argument is supported by research demonstrating that more negativity in adolescents' versus parents' perceptions of parental monitoring is associated with greater adolescent depressive symptoms (De Los Reyes et al 2008) and rule-breaking behavior (De Los Reyes et al 2010). Similarly, more negativity in adolescents' versus parents' perceptions of parenting behavior is associated with greater adolescent internalizing problems and less social competence (Guion et al 2009).…”
Section: Introductionmentioning
confidence: 89%
“…Recent research has demonstrated that the informant discrepancy is also due to both informants' depression (De Los Reyes, Goodman, Kliewer, & Reid-Quiñones, 2008). The current study follows the recognition that internalizing problems are preferably measured by the adolescents' perspective alone.…”
Section: Power Assertive Discipline and Attachmentmentioning
confidence: 99%
“…In Kerr and Stattin's (2000) study, there was only about 20% shared variance between adolescents' and parents' reports of children's disclosure (r=.45). In other studies, the correlation was even lower: r=.23 or 5% shared variance (De Los Reyes et al 2008) and r=.21 or 4% shared variance (Laird et al 2010). A potential explanation for the difference between children's disclosure reported by mothers and adolescents is related to the nature of the samples.…”
Section: Mother-adolescent Agreement On Child Disclosurementioning
confidence: 74%
“…To fill this gap, our study focused on immigrants' and natives' mother-adolescent agreement on children's disclosures. Children's disclosures can be seen as the result of mutual communication processes between parents and children that are driven by both these sources (De Los Reyes et al 2008;Kerr and Stattin 2000).This understanding goes beyond existing research with immigrants, which often assumes that mother-child agreement is the result of transmission from parents to children (e.g., Schönpflug 2009). The premise behind this study was that, if the adaptation of adolescent immigrants to a new cultural setting does indeed undermine parent-child relationships, we should see lower mother-adolescent Mother-Adolescent Agreement 16 agreement on children's disclosure compared to that found among natives, an indication that parent-child communication in immigrant families is to some extent less optimal compared to that in families without acculturation-related challenges.…”
Section: Discussionmentioning
confidence: 99%